Determination of the Contents of Antioxidants and Their Degradation Products in Sodium Chloride Injection for Blood Transfusion - Bo Tao; Gang Wang; Zongning Yin; Xiaocong Pu; Yan Jiang; Luohong Zhang; Jie Cheng; Yong Li; Jiayu Zhang (Journal of Analytical Methods in Chemistry)
The infusion bag is mainly made up of polyolefin polymer. Antioxidants are usually added to these polymer materials in the production process to prevent the materials from aging and enhance the stability of the materials. Because of the potential harm of antioxidants to human body, it is necessary to limit the amount of antioxidants migrating to the pharmaceutical solutions. In the present study, we developed and validated the HPLC method for the simultaneous quantification of antioxidants and their degradation products migrating to sodium chloride solution for injection. A total of six antioxidants and six their degradation products were separated and simultaneously determined by using a Waters Symmetry RP18 column (250 × 4.6 mm, 5 μm) and gradient elution of methanol/acetonitrile/acetic acid-water (1 : 99, v/v) at a flow rate of 1.0 mL/min. The detective wavelength was set at 277 nm, and the column temperature was maintained at 35°C. The method was validated in terms of limit of detection (LOD, 0.011–0.151 μg/mL), limit of quantification (LOQ, 0.031–0.393 μg/mL), intraday precision (0.25%–3.17%), interday precision (0.47%–3.48%), linearity (0.1–46.8 μg/mL, r > 0.9994), stability (0.35%–3.29%), and accuracy (80.39%–104.31%). In the extraction experiment, antioxidants, BHT, 1010, 1330, 1076, and 168, and their degradation products, 1310 and DBP, were detected in the packaging materials. Only 1310 was detected in the migration experiment. The maximum daily dosage of sodium chloride for blood transfusion is three bags, and the content of 1310 in long-term testing samples is from 0 to 12 months ranging from 37.44 μg/3 bags to 48.71 μg/3 bags. The daily intake of 1310 did not exceed 48.71 μg, which was much lower than its permitted daily exposure (PDE, 300 μg/day). Therefore, the antioxidants and their degradation products migrating into the drug solution would not cause drug safety risks.